22+8(4x-4)=10(2x-1)

Simple and best practice solution for 22+8(4x-4)=10(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22+8(4x-4)=10(2x-1) equation:


Simplifying
22 + 8(4x + -4) = 10(2x + -1)

Reorder the terms:
22 + 8(-4 + 4x) = 10(2x + -1)
22 + (-4 * 8 + 4x * 8) = 10(2x + -1)
22 + (-32 + 32x) = 10(2x + -1)

Combine like terms: 22 + -32 = -10
-10 + 32x = 10(2x + -1)

Reorder the terms:
-10 + 32x = 10(-1 + 2x)
-10 + 32x = (-1 * 10 + 2x * 10)
-10 + 32x = (-10 + 20x)

Add '10' to each side of the equation.
-10 + 10 + 32x = -10 + 10 + 20x

Combine like terms: -10 + 10 = 0
0 + 32x = -10 + 10 + 20x
32x = -10 + 10 + 20x

Combine like terms: -10 + 10 = 0
32x = 0 + 20x
32x = 20x

Solving
32x = 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
32x + -20x = 20x + -20x

Combine like terms: 32x + -20x = 12x
12x = 20x + -20x

Combine like terms: 20x + -20x = 0
12x = 0

Divide each side by '12'.
x = 0

Simplifying
x = 0

See similar equations:

| 18x-(2x-9)=41 | | 30+9x=26.76 | | 4x-2-x=-2x-5-5x | | 5-2y=2(y+4) | | 10=18-2q | | -3(x+2)-2=-14 | | 19-5x=-51 | | 6(a+b)=54 | | 7*-8x+4=3x+2 | | 9y+7-5y=9+3y-5 | | 2x^2+x^2-5x+2=0 | | 3p^2+15p+18=0 | | -96v+108=-12(7+8v)-4 | | 2x+x^2=x^2+6 | | n^2+9n-300=0 | | -(n-8)=7n-6(n-1) | | 3x+5+21x+3=176 | | -7(1-7k)=7(-11+5k) | | (62.9291*(y-1))+(64.9278*y)=63.546 | | 1-2x-5=4x-3 | | 2(x-1)=4(x-5) | | -10-10k=-(7k-6)-3(-8+k) | | 5c^3+5c^2-60c=0 | | -6(x+5)=18 | | 19x+2y=17 | | 60-3m=19(4+11m) | | x+5+x-1=90 | | 10x+25y=14.50 | | 44+n=7(10n-2)-11 | | 7(x-5)=28 | | -3(-9n+12)+12=6(n+10) | | 8x-2x+3=20+1 |

Equations solver categories